“Determinación de los estándares de calidad de la fibra de bombonaje (carludovica palmata) para su utilización en la fabrica de sombrero” - Torres Goicoechea,Julia Anne (2001)
There is a great number of vegetal species in the Peruvian Amazon Rainforest. In spite of their great importance and economic interest, they are not properly exploited or even not exploited at all. So, it' s necessary to investigate them in order to make them produce an economic profit, without affecting the delicate ecological system. Plants which produce vegetal fibers are absolutely useful for mankind. One of their products is the 'Paja Toquilla' or 'bombonaje' (for it's name in Spanish) (Carludovica palmata), from which a natural and ecological vegetal fiber is obtained, which is used to make hats and another similar handcraft, which are, nowadays, of great economic interest and demand in the international market. On the other hand, we know that our manufacture industry in SAN MARTIN (north east, PERUVIAN Jungle ), depends more and more on international markets. The international quality standard is superior than ours. So, our industry is in trouble. Our aim is to show the quality standards and the physic and chemical qualities. of this fiber, which would be useful to those, an important number of inhabitants,in the RIOJA Province, who work making handcraft and souvenirs. The samples were taken from a natural cultivation, from TONCHIMA river shores, in the RIOJA province, corresponding to three different ages of the plant hearts (27, 35 and 45 days of development). Each of these samples were treated in four different ways, following four different procedures in order to obtain 'the fiber' (after 0,5,10 and 15 minutes boiling). In the present project, we used two methods: the traditional one, in which we had Maximum and minimum boiling periods of time (5 minutes and 15 minutes). And, in Second place, our method which suggests how to obtain the fiber without boiling the Plants hearts. Both methods were used for the three ages of harvesting, 12 samples in Total to be evaluated according to the local handcraft small industry. The results of our experiments were checked in the local handcraft market. Color, Texture and break resistance, were evaluated according to harvesting time and boiling Time. The chemical analysis shows the following percentages: 44.2% for alpha-cellulose, 14.9% for hemicelluloses, 19.4% for lignin, 6.3% for ash and 17.2% for extractable Elements. The best mechanical and physical qualities like: lighter white, more break resistance, more smppthness, in normal environmental conditions were obtained in samples treated without boiling. A group of experts in handcraft, from RIOJA province, finally decided that the best Fiber obtained was the one harvest after 35 days and without boiling it. Brest color: lighter white; more break resistance and more smoothness.